Underestimated diversity: A new species of the genus Cuneopsis (Bivalvia, Unionidae, Unioninae) from Henan, China - Kaiyu Hou; Xianan Wang; Fang Nan; Ruiwen Wu (Zoosystematics and Evolution)
The global decline of freshwater mussels and their crucial ecological services highlights the necessity and urgency of developing and guiding conservation efforts for this group. Accurately delineating species and understanding their phylogeny are crucial to the core of species conservation. Here, we integrate shell morphology, soft-body anatomy, and molecular systematics to describe a new species of freshwater mussel from the Shi River in Xinyang City, Henan Province, China, i.e., Cuneopsis celtiosimilis sp. nov. Morphologically, this new species resembles its congeneric species C. kiangsiensis and C. celtiformis in shell size, shape, and sculpture. However, this new species can be distinguished from closely related congeners by the pseudocardinal teeth. For the new species, two pseudocardinal teeth of the left valve join together to form a continuous strip; the single pseudocardinal tooth on the right valve is more squashed and lower; the papillae of the incurrent aperture are shorter, forming a pyramidal shape and arranged in two rows. Molecularly, based on the mitochondrial barcoding gene cytochrome c oxidase subunit I (COI), the minimum genetic distance between the new species and other known congeners is 4.6% (C. celtiosimilis sp. nov. vs. C. kiangsiensis). Additionally, the complete mitogenome of C. celtiosimilis sp. nov. was also assembled and annotated. Based on the mitochondrial phylogenomic analyses, the results clarify the phylogenetic position of the new species and establish the most comprehensive phylogenetic relationship of the genus Cuneopsis to date, as follows: ((((C. demangei + C. heudei) + C. szechenyii) + ((C. kiangsiensis + C. celtiosimilis sp. nov.) + C. celtiformis)) + C. rufescens). The discovery of this new taxon contributes to the existing knowledge on freshwater mussels in China, and a key to all known species of Cuneopsis is provided to aid the identification of species in this understudied genus.